“The Colossal Fabric’s Form”: Remodelling Memory, History, and Forgetting in Byron’s Poetic Recollections of Ruins - Sandy, Mark (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay reads Byron’s personal and historical reflections in Manfred and Childe Harold’s Pilgrimage through Nietzsche’s meditations on memory and forgetting in Untimely Meditations. These poetic recollections are explored as moments of wilful erasure. Central to Nietzsche’s thoughts “On the Use and Disadvantages of History for Life” is how single moments are forgotten only to be unwillingly recalled at some future present historical moment. Byron’s desire to forget biography and history, paradoxically, produces a capacity to remember. Byron’s meditations on historical ruins become his own imaginative reflections on both the impulse to, and impossibility of, recovering historical and personal origins or securing an authorial posthumous reputation.